Sequential transarterial chemoembolization and portal vein embolization before resection is a valid oncological strategy for unilobar hepatocellular carcinoma regardless of the tumor burden. Issue 8 (August 2016) - Ronot, Maxime; Cauchy, François; Gregoli, Bettina; Breguet, Romain; Allaham, Wassim; Paradis, Valérie; Soubrane, Olivier; Vilgrain, Valérie
Abstract: Objective: To investigate the long-term oncological outcome of patients with resectable hepatocellular carcinoma (HCC) undergoing sequential transarterial chemoembolization (TACE) and portal vein embolization (PVE). Methods: Analysis of all Child A HCC patients who underwent TACE-PVE before major liver resection from 2006 to 2012 was performed according to whether or not they underwent surgical resection as planned. Results: 54 patients (50 men, 93% median 69-years (range 44–87)) were included. Thirty-nine (72%) patients underwent resection, including 19/25, 16/23, and 4/6 of patients with BCLC A, B, and C (p = 0.839). Twenty-two (56%) had tumor recurrence (median delay 10 months) including 9/19, 11/16, and 2/4 of the patients with BCLC A, B, and C (p = 0.430). Survival was significantly better in resected patients as compared to those who were not resected (median overall survival (OS): 44 vs. 18 months; p < 0.001). Recurrence was associated with a poorer prognosis as compared to patients without recurrence (median OS 43 months vs. not reached; p < 0.001). BCLC stage did not influence survival (p = 0.13). Conclusion: In patients with large unilobar HCC, TACE-PVE leads to resection in most patients, with a good oncological outcome regardless of the tumor burden. When this strategy fails, patients can be managed with TACE despite prior PVE.